Contribution of kinetic electrons to GAM damping. (November 2018) - Ehrlacher, C.; Garbet, X.; Grandgirard, V.; Sarazin, Y.; Donnel, P.; Caschera, E.; Ghendrih, P.; Zarzoso, D.
Abstract: We quantify the contribution of kinetic electrons to GAM damping. This contribution is not negligible due to a resonance between barely trapped/passing electrons bounce/transit frequency and the mode pulsation.